Long-distance systemic signaling and communication in plants - Baluška František (Signaling and Communication in Plants,, 2013)
Our view of plants is changing dramatically. Rather than being only slowly responding organisms, their signaling is often very fast and signals, both of endogenous and exogenous origin, spread throughout plant bodies rapidly. Higher plants coordinate and integrate their tissues and organs via sophisticated sensory systems, which sensitively screen both internal and external factors, feeding them information through both chemical and electrical systemic long-distance communication channels. This revolution in our understanding of higher plants started some twenty years ago with the discovery of systemin and rapid advances continue to be made. This volume captures the current 'state of the art' of this exciting topic in plant sciences.